1995
DOI: 10.1177/107769909507200118
|View full text |Cite
|
Sign up to set email alerts
|

Images of Rosie: A Content Analysis of Women Workers in American Magazine Advertising, 1940–1946

Abstract: This study, based on a content analysis of magazine advertising images of women during the World War 11 era, has two purposes. One is to help determine whether advertisers made a concerted change in their shaping of womenS images during and after World War 11. The other purpose is to indicate further research on the topic of women and advertising during the waryears. This examination is an initial attempt to better explain the relationship between the advertising industry, the actual "reality" of working women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Content analysts have given particular attention to the depiction of women in magazine advertisements (Belkaoui and Belkaoui 1976;Busby and Leichty 1993;Courtney and Lockeretz 1971;Demetrulias and Rosenthal 1985;Easton and Toner 1983;Englis, Solomon, and Ashmore 1994;Lewis and Neville 1995;Poe 1976;Reese, Whipple, and Courtney 1987;Rudman and Hagiwara 1992;Sexton and Haberman 1974;Sullivan and O'Connor 1988;Venkatesan and Losee 1975;Wagner and Banos 1973;Weinberger, Petroshius, and Westin 1979;Zhou 1992). This research has provided detailed information about women's images in magazine ads and has documented changes over time in the nature of their portrayals.…”
mentioning
confidence: 98%
“…Content analysts have given particular attention to the depiction of women in magazine advertisements (Belkaoui and Belkaoui 1976;Busby and Leichty 1993;Courtney and Lockeretz 1971;Demetrulias and Rosenthal 1985;Easton and Toner 1983;Englis, Solomon, and Ashmore 1994;Lewis and Neville 1995;Poe 1976;Reese, Whipple, and Courtney 1987;Rudman and Hagiwara 1992;Sexton and Haberman 1974;Sullivan and O'Connor 1988;Venkatesan and Losee 1975;Wagner and Banos 1973;Weinberger, Petroshius, and Westin 1979;Zhou 1992). This research has provided detailed information about women's images in magazine ads and has documented changes over time in the nature of their portrayals.…”
mentioning
confidence: 98%
“…Such research as Coffman's (1976) study of displays of gender in advertisements; Williamson's (1978Williamson's ( / 1995 study of the content and context of advertisements; Gross and Sheth's (1989) study of time in advertising; Bolla's (1990) study of images of women and leisure in advertising; McCullough's (1993) study of leisure themes in international advertising; Lewis and Neville's (1995) study of the images of women in advertising through World War II; Albanese's (1996, 1997) study of the images of men pictured alone in advertisements; and Sirakaya and Sonmez' s (2000) study of male-female relationships in US state vacation packages can be drawn upon to influence code sheet development.…”
Section: Content Analysis Codingmentioning
confidence: 98%
“…With large data sets, at least 5 per cent of the advertisements should be (re)coded by multiple analysts (Gross and Sheth 1989;Kaid and Wadsworth 1989;Lewis and Neville 1995), while some argue that between 10 per cent and 20 per cent of the body of content should be re-tested (Wimmer and Dominick 1997). Regarding the selection of content for recoding, Riffe et al (1998), suggest that content samples for reliability testing be randomly selected.…”
Section: Content Analysis Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this study further concluded that advertisements published in 1970 characterized women as being dependent on men, as not making important decisions, as having a place only in the home, and as being regarded primarily as sex objects. Over the next two decades or so, several replicative or follow-up studies were conducted using the same methodology (Belkaoui and Belkaoui, 1976;Busby and Leighty, 1993;Kerin et al, 1979;Lewis and Neville, 1995; JOURNAL OF INTERNATIONAL CONSUMER MARKETING 52 Lundstrom and Sciglimpaglia, 1977;Pingree et al, 1976;Sexton and Haberman, 1974;Sullivan and O'Conner, 1988;Venkatesan and Losco, 1975;Wagnet and Banos, 1973). A general conclusion derived from these studies is that the same stereotyping in the portrayals of women continued during the 1970s, however, from the 1980s to the 1990s, the portrayal of women as subordinate to men decreased somewhat, but their portrayal as alluring sex objects increased.…”
Section: Women's Role As Portrayed By Advertisementsmentioning
confidence: 99%